2021
DOI: 10.1107/s2052520621011458
|View full text |Cite
|
Sign up to set email alerts
|

Kilobytes of kilopascals: high-pressure depositions of the Cambridge Structural Database

Abstract: The Cambridge Structural Database (CSD) is the largest repository of crystal structures of organic and metal–organic compounds, containing over 1.1 million entries. Over 3300 of the deposits are structures determined under high pressure, with the number being strongly affected by the experimental requirements of the high-pressure techniques. Nevertheless, it still presents a population sufficiently representative for statistical data mining. In this work, an in-depth analysis of this population is presented, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Recently, research interest in the properties of molecular crystals under high pressure has continued to rise. , External high pressure reduces intermolecular distances, enhances intermolecular and intramolecular interactions, modifies properties, and induces structure phase transformation in molecular crystals . High-pressure research methods typically include both experimental and computational components. The experimental method based on diamond anvil cells (DAC) generates a high-pressure environment for a sample and can provide the evolution of phase transitions, atomic coordinates, and unit cell parameters of molecular crystals, combined with synchrotron XRD, Raman and infrared spectroscopy, photoluminescence, etc. Computational methods, including density functional theory (DFT) and force field (FF) groups, can provide the energetic characteristics of investigated materials and explain the nature of phase transitions on the basis of the critical parameters from experimental measurements for molecular crystals. , Significant progress in engineering made these experiments possible and even routine in some sense, but they were still very time-consuming and complicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, research interest in the properties of molecular crystals under high pressure has continued to rise. , External high pressure reduces intermolecular distances, enhances intermolecular and intramolecular interactions, modifies properties, and induces structure phase transformation in molecular crystals . High-pressure research methods typically include both experimental and computational components. The experimental method based on diamond anvil cells (DAC) generates a high-pressure environment for a sample and can provide the evolution of phase transitions, atomic coordinates, and unit cell parameters of molecular crystals, combined with synchrotron XRD, Raman and infrared spectroscopy, photoluminescence, etc. Computational methods, including density functional theory (DFT) and force field (FF) groups, can provide the energetic characteristics of investigated materials and explain the nature of phase transitions on the basis of the critical parameters from experimental measurements for molecular crystals. , Significant progress in engineering made these experiments possible and even routine in some sense, but they were still very time-consuming and complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research interest in the properties of molecular crystals under high pressure has continued to rise. 1,2 External high pressure reduces intermolecular distances, enhances intermolecular and intramolecular interactions, modifies properties, and induces structure phase transformation in molecular crystals. 3 High-pressure research methods typically include both experimental and computational components.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Numerous studies have shown that extreme pressure can significantly affect the structure of MOFs, , with the earliest high-pressure depositions in the MOF subset of the Cambridge Structural Database (CSD) dating back to 2006 . Since then, the number of high-pressure CN structures deposited in the CSD has grown exponentially and now exceeds 750 . High-pressure investigation of CNs allows us to assess their stability, fracture toughness, elasticity, stiffness, and hardness, factors affecting their possible applications .…”
Section: Introductionmentioning
confidence: 99%